KEPERCAYAAN, e-KUALITAS PELAYANAN, CITRA, KEPUASAN: ANTESEDEN LOYALITAS PELANGGAN PADA MARKETPLACE DI INDONESIA - Sriyanto Sriyanto; Fajar Harimurti (Universitas YPPI Rembang, 2023)
This study aims to analyze the effect of trust, e-service quality, and image on customer loyalty through customer satisfaction as a mediator variable. Sample 200 respondents are customer who are transaction on the marketplace in Indonesia. Data collection using a closed questionnaire was measured by a 5-point Likert scale. The analysis method uses path analysis and Sobel test. The results showed (1) trust, e-service quality, and image had a significant effect on customer satisfaction (2) trust, e-service quality, and image had a significant effect on customer loyalty (3) customer satisfaction had a significant effect on customer loyalty (4) trust and image had a significant effect on customer loyalty through customer satisfaction as modiator variable, while e-service quality have no significant effect on customer loyalty through customer satisfaction as mediator variable. Keywords: trust, service, image, satisfaction, loyalty